Pengaruh Beban Kerja, Motivasi Kerja dan Lingkungan Kerja terhadap Kualitas Pelayanan melalui Engagement pada Perawat di Rumah Sakit: The Influence of Workload, Work Motivation, and Work Environment on Service Quality Through Engagement Among Nurses in Hospitals - Imam Santoso; Yuhelmis; Kusuma Hartono, Risky (Journal of Public Health Education, 2025)
Introduction: The quality of nursing services is influenced by multiple factors, including workload, work motivation, and the work environment. Nurse engagement, as a positive psychological state, may mediate the relationship between these factors and service quality. Objectives: This study aims to examine the effects of workload, work motivation, and work environment on nursing service quality through engagement among nurses at Bhayangkara Brimob Hospital. Method: A quantitative study with a survey design and path analysis was conducted involving 142 nurses selected through total sampling. Data were collected using a validated and reliable questionnaire. Statistical analyses included linear regression and path analysis. Result: Workload had a negative effect on service quality (β = –0.252; p < 0.003) and engagement (β = –0.344; p < 0.000). Work motivation positively affected service quality (β = 0.405; p < 0.000) and engagement (β = 0.472; p < 0.000). The work environment positively influenced service quality (β = 0.742; p < 0.000) and engagement (β = 0.322; p < 0.003). Engagement significantly improved service quality (β = 0.475; p < 0.000). Mediation analysis showed that workload and motivation had indirect effects on service quality through engagement, while the work environment did not demonstrate a significant indirect effect. Conclution: Workload, work motivation, and work environment significantly influence nursing service quality. Engagement mediates the effects of workload and motivation but does not mediate the influence of the work environment.